One-pot four-component reaction for convenient synthesis of functionalized 1-benzamidospiro[indoline-3,4'-pyridines] - Wang, Chao; Jiang, Yan-Hong; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2014)
The one-pot four-component reaction of benzohydrazide (2-picolinohydrazide), acetylenedicarboxylate, isatins and malononitrile (ethyl cyanoacetate) with triethylamine as base catalyst afforded functionalized 1-benzamidospiro[indoline-3,4'-pyridines] in good yields. 1H NMR spectra indicated that an equilibrium of cis/trans-conformations exist in the obtained products.
Keywords: acetylenedicarboxylate; benzohydrazide; 1,4-dihydropyridine; multicomponent reaction; one-pot reaction; spiro[indoline-3,4'-pyridine]